2017
DOI: 10.2340/16501977-2229
|View full text |Cite
|
Sign up to set email alerts
|

Robotic devices and brain-machine interfaces for hand rehabilitation post-stroke

Abstract: This review provides novel insights into the use of robotics in physiotherapy practice, and may help system designers to develop new devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…In fact, these devices allow to increase of the amount and intensity of the therapy, to standardize the treatment, providing a complex but controlled multisensory stimulation [9,10] and helping the patient to complete the required task while preventing inappropriate movements [11]. Even if most of the robots focuses on the more proximal joints (shoulder and elbow) [12], some devices have been specifically developed to target the hand, using either end-effector [13][14][15] or exoskeleton [16,17] design, with encouraging results in terms of motor recovery [12,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these devices allow to increase of the amount and intensity of the therapy, to standardize the treatment, providing a complex but controlled multisensory stimulation [9,10] and helping the patient to complete the required task while preventing inappropriate movements [11]. Even if most of the robots focuses on the more proximal joints (shoulder and elbow) [12], some devices have been specifically developed to target the hand, using either end-effector [13][14][15] or exoskeleton [16,17] design, with encouraging results in terms of motor recovery [12,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that users' requirements, e.g., weight, comfort, aesthetics, and cost are directly related to the success or failure of hand rehabilitation devices [12]. Some researches [13] suggest that the maximum weight of the exoskeleton over the hand should not exceed 500 g. In a review by [14], all exoskeletons surveyed weighed less than 285 g over the hand.…”
Section: Hand Exoskeletonsmentioning
confidence: 99%
“…Cervera et al [36] performed a metaanalysis on the clinical effectiveness of BCI-based stroke therapy among 9 randomised clinical trials (RCT). McConnell et al [37] reviewed and provided insights from a total of 110 robotic devices with brain-machine interfaces for hand rehabilitation post-stroke. These reviews, in general, have reported that such systems provide improvements in both functional and clinical outcomes in pilot studies or trials involving small sample sizes.…”
Section: Introductionmentioning
confidence: 99%